Law Enforcement Factors in Waste Management to Achieve Environmental Sustainability and Community Welfare - Suwari Akhmaddhian; Ria Virigianti; Erga Yuhandra (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2021)
Environmental issues are interesting subjects that are related to the earth’s sustainability. While Garbage is basically an obstacle, it also has the potential to prevent environmental damage and increase the community's economy if it is well managed. This research aims to analyze local government policies in waste management based on the value of ecological justice to achieve natural preservation. The research method used is qualitative with primary data from interviews and observations supported by laws and regulations related to waste management. The research was conducted in Kuningan Regency and Ciamis Regency. The results showed that the Ciamis local government policy in waste management was equipped with local regulations, government officials, infrastructure, community participation, and program innovation, namely waste sorting, waste bank, maggot, and garbage alms. The conclusion is that local government policies, especially in Kuningan, still need improvement related to optimizing the role of the local government in institutional and funding of waste management and increasing public education regarding waste management. Good waste management can create environmental sustainability and community welfare.